2011
DOI: 10.1242/jcs.074963
|View full text |Cite
|
Sign up to set email alerts
|

Activation of metabotropic GABA receptors increases the energy barrier for vesicle fusion

Abstract: SummaryNeurotransmitter release from presynaptic terminals is under the tight control of various metabotropic receptors. We report here that in addition to the regulation of Ca 2+ channel activity, metabotropic GABA B receptors (GABA B Rs) at murine hippocampal glutamatergic synapses utilize an inhibitory pathway that directly targets the synaptic vesicle release machinery. Acute application of the GABA B R agonist baclofen rapidly and reversibly inhibits vesicle fusion, which occurs independently of the SNAP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…In animal studies, it has been shown that the ACC is closely involved in novel object recognition during a task (Weible et al, 2009(Weible et al, , 2012. Specifically, the microinfusion of muscimol, a GABA A receptor agonist, into the ACC immediately before the retrieval phase decreases exploratory behavior toward novel objects (Pezze et al, 2017). In our present and previous studies, Fabp3 KO mice exhibited decreased performance in noveltyseeking (Shimamoto et al, 2014;Yabuki et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…In animal studies, it has been shown that the ACC is closely involved in novel object recognition during a task (Weible et al, 2009(Weible et al, , 2012. Specifically, the microinfusion of muscimol, a GABA A receptor agonist, into the ACC immediately before the retrieval phase decreases exploratory behavior toward novel objects (Pezze et al, 2017). In our present and previous studies, Fabp3 KO mice exhibited decreased performance in noveltyseeking (Shimamoto et al, 2014;Yabuki et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…Recent evidence suggests that neural transmission may be a function of thermodynamic energy barriers to physiological mechanisms (Rost et al, 2011 ) which are as yet not understood. For example, one such physiological barrier is the well-known case of vesicular fusion at axon terminals, the biophysical rate-limiting step of neurological transmission.…”
Section: Brain Temperature and Parenchymamentioning
confidence: 99%
“…GABA B receptors are heteromeric G‐protein‐coupled receptors composed of one GABA B R1 subunit and one GABA B R2 subunit (Kaupmann et al ., ; White et al ., ; Kuner et al ., ; Ng et al ., ). At presynaptic sites, GABA B receptors suppress release by inhibiting voltage‐gated calcium channels (Dolphin & Scott, ) and directly impeding synaptic vesicle exocytosis (Blackmer et al ., ; Yoon et al ., ; Rost et al ., ), while at the postsynaptic membrane they constrain excitability by activating an inward‐rectifying potassium conductance (Newberry & Nicoll, ,b; Gahwiler & Brown, ; Luscher et al ., ) in addition to inhibiting voltage‐gated calcium channel activity and NMDA receptor calcium signalling (Mintz & Bean, ; Perez‐Garci et al ., ; Chalifoux & Carter, , ; Lur & Higley, ).…”
Section: Synaptic and Neuromodulatory Control Of The Gpementioning
confidence: 99%